2002
DOI: 10.1104/pp.012336
|View full text |Cite
|
Sign up to set email alerts
|

Functional Specialization of Maize Mitochondrial Aldehyde Dehydrogenases

Abstract: The maize (Zea mays) rf2a and rf2b genes both encode homotetrameric aldehyde dehydrogenases (ALDHs). The RF2A protein was shown previously to accumulate in the mitochondria. In vitro import experiments and ALDH assays on mitochondrial extracts from rf2a mutant plants established that the RF2B protein also accumulates in the mitochondria. RNA gel-blot analyses and immunohistolocation experiments revealed that these two proteins have only partially redundant expression patterns in organs and cell types. For exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 73 publications
1
62
0
1
Order By: Relevance
“…Under conditions of rapid growth and sufficient oxygen, acetaldehyde will either be used for biosynthetic purposes or respired to CO 2 . The K m of ALDH for acetaldehyde is two orders of magnitude lower than that of ADH Liu and Schnable, 2002). If this is true in pollen, oxidation of acetaldehyde will be highly favored, and the main function of ADH may be to prevent the accidental accumulation of reactive acetaldehyde.…”
Section: The In Vivo Function Of Pdc2 Is To Bypass Pdhmentioning
confidence: 99%
“…Under conditions of rapid growth and sufficient oxygen, acetaldehyde will either be used for biosynthetic purposes or respired to CO 2 . The K m of ALDH for acetaldehyde is two orders of magnitude lower than that of ADH Liu and Schnable, 2002). If this is true in pollen, oxidation of acetaldehyde will be highly favored, and the main function of ADH may be to prevent the accidental accumulation of reactive acetaldehyde.…”
Section: The In Vivo Function Of Pdc2 Is To Bypass Pdhmentioning
confidence: 99%
“…The isolation of Rf2a, a maize nuclear restorer gene of cytoplasmic male sterility, revealed that it encodes a mitochondrial class-2 ALDH (Cui et al 1996). RF2a has been demonstrated to be involved in anther development and plays a critical role in producing functional male gametes (Liu et al 2001;Liu and Schnable 2002). In plants, very few enzymatic pathways that reduce aldehyde accumulation have been defined.…”
Section: Introductionmentioning
confidence: 99%
“…Op den Camp and Kuhlemeier (1997) in tobacco and Skibbe et al (2002) in Arabidopsis showed that ALDHs convert acetaldehyde to acetate in vitro. In addition, Liu and Schnable (2002) demonstrated through an in-depth analysis a functional specialization of the two maize mitochondrial ALDHs. Similarly, the putative mitochondrial located ALDH2B7 of Arabidopsis might be involved in an ABA-mediated response to dehydration.…”
Section: Arabidopsis Aldhs: a Function In Detoxification Of Products mentioning
confidence: 99%